The nexus between export diversification, imports, capital and economic growth in the United Arab Emirates: An empirical investigation - Saima Shadab (Cogent Economics & Finance, 2021)
Using the Vector Error Correction Model (VECM) and Toda-Yamamoto Causality approach, this paper investigates the short-run and long-run relationship between export diversification, physical and human capital, imports, and economic growth in the UAE. The study period in consideration is 1975-2017. The findings obtained from the VECM test confirm the existence of a significant long-run relationship between export diversification, imports, and economic growth in the UAE. Besides, the Toda Yamamoto Granger Causality test results reveal that imports Granger-cause UAE's economic growth which proves the validity of the Import-Led Growth hypothesis for the UAE economy in the long-run. The results also confirm that a unidirectional causal relationship exists from export diversification to economic growth for the UAE. This finding indicates the success of the UAE economy in attaining economic diversification and reduction in oil-dependency.
Keywords: 330; economic growth; export diversification; granger causality; VECM